A new air‐stable and reusable tetraphosphine ligand for rhodium‐catalyzed hydroformylation of terminal olefins at low temperature. (19th November 2018) - Zhou, Fanding; Zhang, Lin; Wu, Qianhui; Guo, Fuya; Tang, Songbai; Xu, Bin; Yuan, Maolin; Fu, Haiyan; Li, Ruixiang; Zheng, Xueli; Chen, Hua
Abstract : Tetraphosphine and bisphosphine ligands were synthesized, characterized and employed in Rh‐catalyzed hydroformylation of 1‐octene and 1‐hexene. Conversion of over 97.7% and aldehyde yield of 94.1% were achieved at 60°C, 20 bar. This remarkable performance could also be retained at lower temperature (i.e. 40°C) by prolonging the reaction time. The tetraphosphine ligand‐modified Rh catalyst could be reused for at least seven successive runs with catalytic activity and selectivity almost unchanged; the catalyst was separated from the products and recycled directly in homogeneous hydroformylation, indicating that the catalyst might have good stability. 31 P NMR and high‐resolution mass spectral characterization hinted that the reason for the reusability of the catalyst might be that the tetraphosphine ligand is relatively air‐stable and is probably slowly oxidized during the recycling runs. The tetraphosphine ligand has four phosphorus atoms to be partially oxidized and could still coordinate with the Rh center via the unoxidized phosphorus atoms to stabilize the catalyst, based on the multiple chelating modes of the tetraphosphine ligand. Hence, the catalytic activity and selectivity could be retained for a certain number of runs. Abstract : A new air‐stable tetraphosphine ligand‐based catalyst could lead to high conversion (>97.7%) and high aldehyde selectivity (>94.1%) at low temperature (40–60°C). Moreover, the tetraphosphine ligand could chelate with Rh due to the multiple chelating modes even though one or two phosphorus atoms were oxidized, providing at least seven reuses of the catalyst in homogeneous hydroformylation.